Lasem in the 13th-18th Centuries Global Cultural Crossroad - Wijaya, Daya Negri; Wahyudi, Deny Yudo; Pratama, Andhika Yudha; Wulandari, Prisca Kiki; Maulidah, Alvin; Fadilla, Firza Azzam (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Lasem, a small town on the north coast of Java, has long been recognized as a meeting point for various global cultures, especially since the heyday of the Nusantara's maritime trade. This article explores Lasem's role as a cultural crossroads between Chinese, Javanese, Arabs and Europeans, which is visible in various aspects of community life, such as art, language, cuisine and local traditions. Through a historical and ethnographic approach, the research highlights how cultural interaction and assimilation in Lasem shaped a unique local identity, while contributing to wider cultural dynamics in Indonesia. The article also discusses the challenges Lasem faces in maintaining its cultural heritage amidst modernization and globalization, as well as the efforts of local communities in preserving their rich history and culture. The results of this research are expected to contribute to a deeper understanding of cultural crossovers and their impact on local identity formation in the Southeast Asian region.